The principle of interculturalism in Ecuadorian legislation - Sánchez Padilla, Patricio (2018)
One of the most challenging situations in current constitutionalism is to reduce discrimination based on intolerance of the essential characteristics of each culture. The Ecuadorian state is a country with wide cultural diversity. That diversity was -and still is, although to a fewer extent- one of the reasons why cultural minorities keep being discriminated. Fostering coexistence between different cultures is a difficult but not impossible task. It is necessary to see diversity as an opportunity to transform inequalities, fostering unity and harmony in plurality, recognizing the principle of equality and inter-culturalism among the people, consolidating egalitarian intercultural relations, restructuring and directing public policies and regulations towards the formal and material recognition of the human rights of all citizens.